CONSPICUOUS CONSERVATION: THE ROLE OF SUSTAINABLE BRAND CHOICES IN SIGNALING IDENTITY AND SOCIAL STATUS - Suharti; Lukmanul Hakim; Dahrul Aman Harahap (RADJA PUBLIKA, 2026)
This article examines the concept of conspicuous conservation, focusing on how sustainable brand choices function as signals of identity and social status in contemporary consumer behavior. As sustainability becomes increasingly visible in the marketplace, consumers are not only motivated by environmental concerns but also by the desire to express values and gain social recognition. Using a narrative literature review, this study integrates insights from marketing, sociology, and consumer psychology to explore the dual role of sustainable consumption as both ethical behavior and symbolic signaling. The findings highlight key themes, including sustainability as identity expression, status signaling through ethical consumption, the role of visibility, and the tension between intrinsic and extrinsic motivations. The study further explains the mechanisms of conspicuous conservation, emphasizing the importance of social comparison, cultural context, and public visibility in shaping consumer behavior. In addition, several moderating factors are identified, such as income, cultural norms, brand credibility, and consumer awareness. A conceptual framework is proposed to illustrate how sustainable choices translate into social recognition and consumer outcomes. The article contributes by linking sustainability with signaling theory and offers practical implications for designing authentic and effective sustainable branding strategies.